On the Norm of the South-West Russia 16th–17th-Century Literary Language - Целунова, Е. А. (Kalbotyra, 1988)
At the end of the 15th century in South-West Russia there appeared books written in the “prosta mova” (literary “simple” language), based on Ukrainian and Byelorussian dialects. One of the books of this kind is the “Kazanie of S. Kirill” (1596), translated from Polish by S. Zizany. The aim of the paper is to find out normative verbal forms in the “Kazanie” and to state the languages by which these forms where prompted to S. Zizany.